An Overview of the Productive Structure of the Amazon Region: Using the Eyes of an Interregional Input-Output System - Joaquim J.M. Guilhoto; Umberto Antonio Sesso Filho (European Regional Science Association (ERSA), 2003)
There is a scarcity of economic studies about the economy of the Amazon region, and specially about its productive structure. The goal of the present study is to shed some light on the way that the productive relations take place among the states of the Amazon region and between them and the rest of Brazil. This study takes as the main source of data an interregional input-output system consisted of 10 regions (nine Amazon states and the Rest of Brazil region) constructed for the year of 1999 by Guilhoto et al. (2002) for the Amazon Bank (BASA). The analysis is conducted by first studying, through the interregional input-output system, how the economic relations take place in the Amazon region. Then, through a series of methodologies, like multipliers, and backward and forward linkages, and using the concept of Electroeconogram it is made a comparative study of the differences in productive structures among the Amazon Region states.
Keywords: 330